2023
DOI: 10.1209/0295-5075/acc3bf
|View full text |Cite
|
Sign up to set email alerts
|

Data-driven inference of complex system dynamics: A mini-review

Abstract: Our ability to observe the network topology and nodes' behaviors of complex systems has significantly advanced in the past decade, giving rise to a new and fast-developing frontier - inferring the underlying dynamical mechanisms of complex systems from the observation data. Here we explain the rationale of data-driven dynamics inference and review the recent progress in this emerging field. Specifically, we classify the existing methods of dynamics inference into three categories, and describe their key ideas,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Currently, the three main classes of methods to learn equations from data are symbolic regression [65], neural-network approaches [13], and library-based sparse regression [12]. Recent reviews of these categories and their overlaps can be found in [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the three main classes of methods to learn equations from data are symbolic regression [65], neural-network approaches [13], and library-based sparse regression [12]. Recent reviews of these categories and their overlaps can be found in [66,67].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, some methods restrict inferences to statistical arguments with uncertainty in order to remove the dependence on a priori information. For the interested reader, a comprehensive review and discussion on data-driven network inference has also been given by Gao & Yan [13].…”
Section: Introductionmentioning
confidence: 99%